Growth rates dependence of macro/microstructures and mechanical properties of Ti-47Al-2Nb-2Cr-0.2Er alloy directionally solidified by cold crucible. (5th July 2017) - Wang, Qiang; Ding, Hongsheng; Zhang, Hailong; Liu, Shiqiu; Chen, Ruirun; Guo, Jingjie; Fu, Hengzhi
Abstract: IntermetallicsTi-47Al-2Nb-2Cr-0.2Er alloys are prepared at different growth rates ranging from 0.6 mm/min to 1.2 mm/min via cold crucible directional solidification with the power of 50 kW. The macro/microstructure evolutions and mechanical properties of the directionally solidified ingots are studied in details. The angles between the columnar grains and the growth direction increase gradually from the center to the edge of the ingot. The lamellae orientations show no distinct variations under the growth rates of 0.6–1.0 mm/min, while the lamellae orientation deviates significantly from the growth direction at the growth rate of 1.2 mm/min. The interlamellar spacing is inverse proportional to the growth rate. The alloy with finer interlamellar spacing shows higher nanoindentation hardness. The corresponding relationship between nanoindentation hardness ( H N ) and interlamellar spacing ( λ ) can be fitted by H N = 36.3 λ − 0.254 . Hindrance of the semi-coherent interface to dislocation movement results in higher tensile strength of the alloy and the larger tensile elongation can be attributed to the improvement of the deformation uniformity. Graphical abstract: Highlights: The columnar grains are inclined to the growth direction. The lamellae are refined with the increase of growth rates. Finer lamellae results in higher nanoindentation hardness. The TiAl alloy with finer lamellae exhibits better tensile performances.